Newborn Periventricular Nodular Heterotopia with Persistent Feeding Cyanosis and Apneic Spell: A Case Report - Seok Jin Hong; Ji Eun Park; Young Bae Sohn; Yoong A Suh; Jang Hoon Lee; Moon Sung Park (Korean Society of Neonatology, 2022)
Periventricular nodular heterotopia (PNH) is a neuronal migration disorder that occurs during early brain development. Patients with PNH may be asymptomatic and have normal intelligence; however, PNH is also known to cause various symptoms such as seizures, dyslexia, and cardiovascular anomalies. PNH is not commonly diagnosed during early infancy because of the lack of clinical manifestations during this period. We present the case of a female infant diagnosed with PNH based on brain magnetic resonance imaging, who had symptomatic patent ductus arteriosus that had to be ligated surgically and had prolonged feeding cyanosis with frequent apneic spells.